Depicting the faces of results-oriented regulatory processes in Portugal: National testing in policy texts. (March 2020) - Carvalho, Luís Miguel; Costa, Estela; Sant'Ovaia, Carlos
This article analyses the trajectory of national testing in Portugal between the early 1990s and 2015 in order to unveil continuities and changes in the regulatory processes of education in Portugal, particularly the emergence of results-based coordination and control methods. Drawing on legislative materials, it identifies and describes the different forms or modalities of national testing and other assessment tools that have been used at basic and secondary school levels. Drawing on the texts of Ministers for Education (from documents and interviews), government programmes, and other official texts concerning the adoption of national testing, it describes and analyses the various ways of interpreting the regulatory rationale based on results of the aforementioned period. The article highlights three main areas of tension around which the different approaches to interpreting these results-oriented regulatory processes are structured in Portugal – accountability models, regulatory models and legitimating principles for the education system – and how they are overcome in the Portuguese context.